Fake News: relación entre los rasgos de personalidad, la influencia social y la susceptibilidad a aceptarlas como reales - De la Oliva Alzamora, Maria Paula (2021)
This research explores the relation between the big five personality factors and the susceptibility to social influence with the susceptibility to accept fake news (disinformation). The understanding of this phenomenon due to individual differences is a barely researched subject. Nevertheless, the massive spread of false information on social media, and its consequences, show the importance of this research. The measurement tools used include a Fake News task, adapted versions of the SPTS (Susceptibility to Persuasion Scale) and the Mini-IPIP (International Personality Item Pool). The psychometric properties of the scores obtained with these scales were examined through the Factorial Analysis and the omega reliability index. Furthermore, by means of a multiple linear regression analysis, two models to predict susceptibility to accept fake news were assessed. The results show that certain personality traits and susceptibility to social influence may be useful predictors of the dependent variable, particularly when social influence is contextualized to the consumption of news on social media. Some corrections for the questionnaires are recommended; moreover, some hypotheses are suggested regarding de interaction of personality, social influence and susceptibility to accepting fake news for further research.